2019
DOI: 10.1107/s2059798318017552
|View full text |Cite
|
Sign up to set email alerts
|

Solution structures of long-acting insulin analogues and their complexes with albumin

Abstract: The lipidation of peptide drugs is one strategy to obtain extended half-lives, enabling once-daily or even less frequent injections for patients. The half-life extension results from a combination of self-association and association with human serum albumin (albumin). The self-association and association with albumin of two insulin analogues, insulin detemir and insulin degludec, were investigated by small-angle X-ray scattering (SAXS) and dynamic light scattering (DLS) in phenolic buffers. Detemir shows conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
(68 reference statements)
0
18
0
Order By: Relevance
“…For example, insulin-like peptides have shown considerably increase in half-life when lipidated [9]. Ryberg et al have shown that the tertiary structure of the HSA-lipidated peptide complex corresponds to hexamers, indicating that the structure of HSA can change as a consequence of API-binding [10].…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%
“…For example, insulin-like peptides have shown considerably increase in half-life when lipidated [9]. Ryberg et al have shown that the tertiary structure of the HSA-lipidated peptide complex corresponds to hexamers, indicating that the structure of HSA can change as a consequence of API-binding [10].…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%
“…The experimental details can be found in Table 1 and Table 2 as well as the Materials and methods section in Ryberg et al 2019. 22 SASREFCV 79,80 (SASREF) was used for rigid body modelling with standard settings for X-ray data and based on data up to q = 0.43 Å -1 . The input structures were the same albumin and detemir hexamer structures that were used for setting up the simulations.…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%
“…The SAXS sample preparation and data collection were carried out as described in Ryberg et al 2019. 22 The samples were titrated with 0-100 mM NaCl. Data analysis and modelling were carried out using the ATSAS Program Package version 2.8.3 82 .…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic proteins (biologics) provide important therapies for a variety of diseases, such as diabetes 1 , cancer 2 , infectious diseases 3 , hemophilia 4 , and anemia 5 . Although liquid formulations are usually preferred for injectable biologics, this form is not always feasible given the high molecular sensitivity of proteins to mechanical stresses, temperature, and other environmental factors that can lead to protein denaturation, aggregation, and degradation 6 .…”
Section: Introductionmentioning
confidence: 99%